The Reversed Rule of Law in the Justice System and the Status of Judges - Muszyński, Mariusz (Reversed Rule of Law in the Creation, Interpretation and Application of Law in Poland: Methods and Consequences, 2026)
The judiciary in Poland had long been identified as requiring reform, both in terms of its organisational structure and the status of judges. The reform was implemented in 2018. These changes were not accepted by the political opposition or the legal community associated with it, including parts of the judicial community. Opponents of the reform received support from international institutions. As a result, these groups began contesting the reforms in an organised manner, including attempts to obstruct the functioning of the reformed institutions. This Chapter presents the actions of judges opposed to the reform and analyses their judicial activities in light of the standards enshrined in the Constitution of the Republic of Poland and Polish statutes. It also reviews international case law (judgments of the Court of Justice of the European Union (CJEU) and the European Court of Human Rights (ECtHR)) concerningthe Polish judicial reform. Since the actions of the judiciary lacked a legal basis in Polish law, judgments of the CJEU and the ECtHR were used as a source of external authorisation and legitimisation. The analysis leads to the conclusion that the Polish judiciary, supported by international tribunals, violates the standards of the rule of law as defined by the Constitution of the Republic of Poland and undermines thelegal and political order of the state.Keywords: judiciary, judicial power, CJEU, ECtHR, National Council of Judiciary, Disciplinary Chamber, judicial independence test